Current Trends of Digital Economy Development in Supply Chain Policy - V. Astakhova, Ekaterina; E. Vannikova, Ekaterina (International Journal of Supply Chain Management, 2019)
Modern trends of development of economy indicate that there is a digital transformation of the international community and the economic environment, which is caused by supply chain policy. The complication of production and public structures and the relations characteristic of modern society put in the forefront a question of formation of digital economy as which fundamentals modern digital technologies act. More and more attention is paid to digital technologies and also new forms of electronic business where human and financial resources of the world collect that undoubtedly confirms relevance and the importance of a subject of a research and cases in point, opening new sides of formation of concepts of economic security of Russia as member of the international community. Systematization of characteristics of category "digital" economy is given in article, the periodization of formation, development of digital technologies in economic space of various sectors of the economy is considered. Ideas of current trends of development of digital economy in various states are considered and systematized; features of digital economy, stages of formation and development are studied; formations of institutional bases of digital economic space which represent set of theoretical bases and procedures of their practical embodiment.